Socialna kompetentnost in učna uspešnost v prvih razredih osnovne šole - Vidmar, Maša (Šolsko polje, 2011)
This longitudinal study investigated the relationship of children's social competence to their academic achievement and vice versa in the fi rst (measure2 M2; N = 325) and second (M4; N = 323) grades of elementary school. Children's teachers assessed social competence at the end of first andsecond grade by completing The Social Competence and Behavior Evaluation Scale (La- Freniere et al., 2001). Children's homeroom teachers assessed academic achievement by evaluating children's attainment of performance standards in Slovenian, mathematics, and social studies/science at M2 (Zupančič, 2006) and M4 (Vidmar in Zupančič, 2007). Structural equation modeling showed support for the reciprocal model of the relationship between academic achievement and social competence; more socially competent first-graders had better academic attainment when they became second-graders (in comparison to less socially competent first-graders) and vice versa: children with higher academic achievement in first grade were described as more socially competent in second grade (compared to first-graders with lower academic achievement). The coefficients of the cross-lagged paths were small in size. Social competence and academic achievement demonstrated high temporal stability and also significant within-time correlations (with the correlation at M2 being higher than the correlation at M4). Maternal education level was included in the reciprocal model as a covariate; the paths to academic achievement and social competence were signifi cant, and other coefficients in this model (i.e. loadings, correlations, and autoregressive and cross-lagged coefficients) remained practically the same as in the model without maternal education level.
Keywords: social competence; socialna kompetentnost; učna uspešnost; academic achievement; elementary school; osnovne šole; začetni pouk; structural equation modeling; strukturno modeliranje; Slovenian; slovenščina; Slovene; mathematics; matematika; social studies/science; spoznavanje okolja